Annealing induced modifications in physicochemical and optoelectronic properties of CdS/CuInGaSe2 thin film. (1st January 2019) - Joshi, Rajesh A.; Gupta, Mukul; Phase, D.M.
Graphical abstract: Highlights: CdS/CIGS thin films deposited by chemical ion exchange method at room temperature. Effect of annealing on interface, composition and surface of CdS/CIGS studied. Annealing at 300 °C suited for modifications of surface, interface and composition. Increase in conversion efficiency observed from 1.05 to 2.96% upon annealing. Abstract: The present article deals with engineering of physicochemical and optoelectronic properties of soft chemical route synthesized CdS/CuInGaSe2 heterojunction thin films upon air annealing at controlled heating rate of 3 °C/min for 100, 200 and 300 °C with the intension to optimize the post deposition treatment parameter for improvising interface between two layers, so as to obtain controlled stoichiometry (composition) and surface structure modifications. These as deposited and annealed heterojunction thin films were characterized for structural, compositional, morphological, optical and electrical characteristics. The structural pattern obtained from X-ray diffraction pattern (XRD) represents rising of new peaks of (2 1 2), (1 0 5) plane, while widening and shifting of peak position (2 0 5) can be observed on annealing at 300 °C, these planer orientation along with (1 1 2), (2 1 1), (2 1 2), (1 0 5) corresponds to chalcopyrite phase of tetragonal CuInGaSe2 materials whereas peak at 21.40° and 30.39° represents CdS and ITO substrate material respectively, the average crystallite size found to be increased from 19 nm to 48 nm on annealing treatment. Elemental composition of as deposited heterojunction thin film confirmed by studying energy dispersive X-ray absorption spectrum (EDAX) which shows presence of peaks corresponding to Cu, Cd, Ga, In, Se and S confirming expected elemental composition. Selected area electron diffraction (SAED) pattern obtained from as deposited thin film shows presence of (1 1 2) and (2 1 1) peaks while nanostructured phase confirmed by transmission electron microscopy (TEM) image. Atomic force microscopy (AFM) images of as deposited and annealed samples when compared, represents grain growth in 300 °C annealed sample, this growth may be due to external energy induced grain agglomeration by polygonization process. Optical absorbance spectra shows blue shift in optical absorbance coefficient while extrapolating for energy band gap (Eg) exhibits red shift from 1.48 eV to 1.21 eV upon annealing. The electrical properties when studied on exposing these as deposited and annealed thin films to 100 mW/cm 2 light source shows an enhancement in conversion efficiency from 1.05 to 2.96% respectively.